Analisis kesulitan guru dalam mengembangkan materi UUD 1945 berbasis putusan Mahkamah Konstitusi - Narmoatmojo, Winarno; Yuliandari, Erna; AR, Machmud; Rusnaini, Rusnaini; Suryaningsih, Anis (Universitas Negeri Manado, 2021)
The decision of the Constitutional Court is a final and binding legal decision that can be used as a source of material for the content of Civics, especially in the scope of the 1945 Constitution material. The method used is descriptive qualitative. Data collection techniques used interviews with PPKn SMP Wonogiri teacher informants and experts in the field of law, document analysis of the PPKN SMP textbooks, and the 2013 Civics Education curriculum, supported by Focus Group Discussion. The results showed that teachers had difficulty in developing the material for the 1945 Constitution based on the decisions of the Constitutional Court. The material for the 1945 Constitution of the Junior High School level Civics is still simple and does not require many sources of material and difficult material such as the decision of the Constitutional Court. The development of materials based on the decisions of the Constitutional Court can be carried out by encountering cases or constitutional problems in the administration of the state that is not contained in other sources of material and limiting the decisions of the Constitutional Court related to constitutional issues, elections, political parties. Teachers can start the introduction material and use the decisions of the Constitutional Court as learning materials with high thinking skills. Therefore, the development of material for the 1945 Constitution based on the decision of the Constitutional Court in the Civics Education subject in junior high schools can be developed according to the stages of thinking of the students.Â Â